(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Green Supply Chain Management (GSCM) is an essential strategy for businesses aiming to integrate sustainability into their supply chain operations. With increasing global awareness of environmental issues such as climate change, resource depletion, and pollution, organizations are shifting towards green practices to mitigate their ecological footprint. GSCM involves incorporating environmentally responsible practices throughout the supply chain, including sourcing, production, distribution, and product lifecycle management. This approach aligns business operations with international sustainability initiatives, regulatory requirements, and consumer expectations for eco-friendly products. The adoption of GSCM offers several advantages, including regulatory compliance, cost savings, and enhanced corporate reputation. Companies that integrate green supply chain strategies benefit from reduced waste, improved resource efficiency, and optimized logistics, leading to long-term financial gains. Moreover, sustainable supply chain practices attract environmentally conscious consumers and stakeholders, providing a competitive advantage in the marketplace. However, despite its numerous benefits, the transition to GSCM poses challenges, such as high implementation costs, resistance to change, and difficulties in supplier collaboration. Technological advancements play a significant role in addressing these challenges by enhancing transparency and efficiency in supply chain operations. Innovations such as artificial intelligence, blockchain, and the Internet of Things (IoT) contribute to better resource management and traceability. Additionally, stakeholder collaboration, policy incentives, and industry partnerships are critical in promoting the adoption of sustainable supply chain practices. As environmental concerns continue to grow, GSCM is poised to shape the future of global supply chains, fostering economic and ecological sustainability.